Digital Alerting and Outcomes in Patients With Sepsis: Systematic Review and Meta-Analysis - Joshi, Meera; Ashrafian, Hutan; Arora, Sonal; Khan, Sadia; Cooke, Graham; Darzi, Ara (JMIR Publications, 2019)
BackgroundThe diagnosis and management of sepsis remain a global health care challenge. Digital technologies have the potential to improve sepsis care. ObjectiveThe aim of this paper was to systematically review the evidence on the impact of digital alerting systems on sepsis related outcomes. MethodsThe following databases were searched for studies published from April 1964 to February 12, 2019, with no language restriction: EMBASE, MEDLINE, HMIC, PsycINFO, and Cochrane. All full-text reports of studies identified as potentially eligible after title and abstract reviews were obtained for further review. The search was limited to adult inpatients. Relevant articles were hand searched for other studies. Only studies with clear pre- and postalerting phases were included. Primary outcomes were hospital length of stay (LOS) and intensive care LOS, whereas secondary outcomes were time to antibiotics and mortality. Studies based solely on intensive care, case reports, narrative reviews, editorials, and commentaries were excluded. All other trial designs were included. A qualitative assessment and meta-analysis were performed. ResultsThis review identified 72 full-text articles. From these, 16 studies met the inclusion criteria and were included in the final analysis. Of these, 8 studies reviewed hospital LOS, 12 reviewed mortality outcomes, 5 studies explored time to antibiotics, and 5 studies investigated intensive care unit (ICU) LOS. Both quantitative and qualitative assessments of the studies were performed. There was evidence of a significant benefit of digital alerting in hospital LOS, which reduced by 1.31 days (P=.014), and ICU LOS, which reduced by 0.766 days (P=.007). There was no significant association between digital alerts and mortality (mean decrease 11.4%; P=.77) or time to antibiotics (mean decrease 126 min; P=.13). ConclusionsThis review highlights that digital alerts can considerably reduce hospital and ICU stay for patients with sepsis. Further studies including randomized controlled trials are necessary to confirm these findings and identify the choice of alerting system according to the patient status and pathological cohort.